Study of TiO2 anatase nano and microstructures with dominant {001} facets for NO oxidation - Sofianou, Maria; Trapalis, C.; Psycharis, V.; Boukos, N.; Vaimakis, T.; Yu, J.; Wang, W. (Springer, 2012)
Introduction: TiO2 anatase nanoplates and hollow microspheres were fabricated by a solvothermal-hydrothermal method using titanium isopropoxide as a titanium precursor and hydrofluoric acid as a capping agent in order to enhance the formation of the {001} crystal facets of the anatase nanocrystals. Methods: These different morphological structures of TiO2 anatase can be achieved by only changing the solvent, keeping the amount of the precursor and of the capping agent identical during the solvothermal-hydrothermal process. Results and discussion: After calcination of the samples, the adsorbed fluoride atoms on the {001} crystal facets of the TiO2 anatase nanocrystals were completely removed from their surface according to XPS analysis. The calcined TiO2 anatase structures were higher crystallized and the specific surface area of the catalysts increased, enhancing their photocatalytic activity in comparison to the non-calcined TiO2 anatase structures. All TiO2 anatase samples with adsorbed as well as non-adsorbed fluoride atoms on their {001} crystal facets, exhibited a higher photonic efficiency than Degussa P25, which was used as a reference. Conclusion: The fluoride free TiO2 anatase nanoplates exhibited the best photocatalytic activity in oxidizing the NO gas to NO2 and NO3-. © 2012 Springer-Verlag.